I Participate; Therefore, I Am (And I Learn): Researching Learners’ Multilingual Identity in the Multilingual School Context - Lujić Rea (Sciendo, 2021)
This study examines the relationship between the participation of multilingual students in FAL (French as an additional language) classroom and language learners’ identities associated with the related community of practice. Classroom participation, a key concept of the study, is defined as a verbal form of learners’ investment in language learning, which can both enhance language learning and change the identity of language learners. The research was conducted in an international multilingual school in Croatia among eight 5th grade multilingual and multicultural students learning French as an additional language. For data collection purposes, French language lessons and twelve video recordings with a total length of approx. 480 minutes were observed and taped. A qualitative analysis of the participation of each student was conducted with the regard to the power relations among members of the classroom. The analysis revealed that, from the chosen theoretical perspective where an additional language is seen both as a tool of power and a tool for power, the identity of language learners can be described as a dynamic combination of some of the following identity positions: a language learner in a position of power, a language learner in a higher position of power than others, a language learner in a reduced position of power but eager for a position of power, a language learner in a reduced position of power but not eager for a position of power. The results of this study are consistent with the main assumptions about the identity of language learners made by other socially oriented authors in SLA (Norton-Peirce, 1995; Pavlenko & Blackledge, 2004; Darvin & Norton, 2015), according to which language learners’ identity is multiple, dynamic, discursively shaped and context-dependent.